2013
DOI: 10.3233/jad-2012-121633
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in MAPT Gene Cause Chromosome Instability and Introduce Copy Number Variations Widely in the Genome

Abstract: In addition to the main function of promoting polymerization and stabilization of microtubules, other roles are being attributed to tau, now considered a multifunctional protein. In particular, previous studies suggest that tau is involved in chromosome stability and genome protection. We performed cytogenetic analysis, including molecular karyotyping, on lymphocytes and fibroblasts from patients affected by frontotemporal lobar degeneration carrying different mutations in the microtubule-associated protein ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 29 publications
5
49
0
Order By: Relevance
“…Similarly, tau knockout neurons are more susceptible to hyperthermia-induced DNA and RNA breakage in comparison to their wild-type counterparts [495]. Furthermore, tau may be involved not only in DNA protection, but also in DNA repair mechanisms [495], although this remains controversial since others have reported that tau is not involved in DNA repair [421]. …”
Section: Tau Localisation In Neuronsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, tau knockout neurons are more susceptible to hyperthermia-induced DNA and RNA breakage in comparison to their wild-type counterparts [495]. Furthermore, tau may be involved not only in DNA protection, but also in DNA repair mechanisms [495], although this remains controversial since others have reported that tau is not involved in DNA repair [421]. …”
Section: Tau Localisation In Neuronsmentioning
confidence: 99%
“…Tau binds to the AT-rich minor groove of DNA through its proline-rich and microtubule binding domains [403, 421]. The typical function of minor groove architectural binding proteins, such as high mobility group proteins, is to alter DNA conformation, causing it to unwind [34].…”
Section: Tau Localisation In Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, Tau has been reported to have a DNA-protective function in the nucleus45. Second, it has been shown that aneuploidy is present in peripheral cells and in primary fibroblast cell cultures from patients carrying known Tauopathies mutations67. Third, in mice, expression of similar Tau mutations also induces genomic instability ranging from chromosome rearrangements to aneuploidy8.…”
mentioning
confidence: 99%